Emotional Value Analysis of the Word of Mouth of Lake Toba Super Priority Tourists with Satisfaction as Intervening Variable - Megasari Gusandra Saragih; Mesra B (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the effect of emotional value on word of mouth mediated by tourist satisfaction. The main problem in this study is the decline in the number of tourist visits to Lake Toba's super priority tourism during the covid-19 pandemic. The number of samples as many as 140 tourists, with a non-probability sampling technique with a purposive sampling approach. This research uses path analysis method with AMOS 24.0. The results of the study found that emotional value and satisfaction had a positive and significant effect on tourist word of mouth in the super priority tourism of Lake Toba. Satisfaction mediates in full mediation the influence of emotional value on word of mouth tourists at the Lake Toba Super Priority tourist attraction.